2014
DOI: 10.1515/cclm-2013-0823
|View full text |Cite
|
Sign up to set email alerts
|

Performance of urinary NGAL and L-FABP in predicting acute kidney injury and subsequent renal recovery: a cohort study based on major surgeries

Abstract: Urinary NGAL and L-FABP can be used to detect AKI and combining NGAL and L-FABP may improve the diagnostic performance; however, NGAL and L-FABP may be poor predictors for renal recovery after AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
(46 reference statements)
1
26
0
2
Order By: Relevance
“…Thus, earlier identification of patients who have not fulfilled the diagnosis of AKI may permit physicians to take appropriate actions. To date, the following biomarkers have been validated for early detection of AKI: sCysC, serum and urine neutrophil gelatinase-associated lipocalin [23,24], kidney injury molecule 1 [25], urinary insulin-like growth factor-binding protein 7 [26], and urinary interleukin 18 [27]. Among these, sCysC is reportedly an early biomarker for diagnosing AKI in patients receiving cardiac surgery [22,28], with liver cirrhosis [29] or sepsis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, earlier identification of patients who have not fulfilled the diagnosis of AKI may permit physicians to take appropriate actions. To date, the following biomarkers have been validated for early detection of AKI: sCysC, serum and urine neutrophil gelatinase-associated lipocalin [23,24], kidney injury molecule 1 [25], urinary insulin-like growth factor-binding protein 7 [26], and urinary interleukin 18 [27]. Among these, sCysC is reportedly an early biomarker for diagnosing AKI in patients receiving cardiac surgery [22,28], with liver cirrhosis [29] or sepsis [24].…”
Section: Discussionmentioning
confidence: 99%
“…This study clearly highlights the value of repeated measures over single values. KIM-1 and L-FABP have also been proposed as a marker of renal recovery after AKI [35, 36]. Similarly the product of the more recently described G 1 cell cycle arrest markers of renal stress TIMP-2 and IGFBP7 ([TIMP-2] × [IGFBP7]) predicted short-term renal recovery/non-recovery within 48 h in 57 patients with early AKI [37].…”
Section: Clinical Definition Of Renal Recoverymentioning
confidence: 99%
“…In a recent study of critically ill patients, urinary L-FABP improved the predictive capability of a clinical prediction model for AKI progression, dialysis, or death within 7 days among patients with early AKI [116]. In addition, among patients undergoing major surgery, Zeng et al described the use of NGAL and L-FABP as a promising combination that may improve the diagnostic performance of AKI detection, although the investigators found this panel of biomarkers to be a poor predictor of renal recovery after AKI [117]. In summary, urinary L-FABP appears to be a promising biomarker for both diagnosis and prediction of AKI and its outcomes among critically ill patients [118].…”
Section: Kidney Injury Moleculementioning
confidence: 99%